Family background, schooling resources, and institutional features: What determines student performance in East Asian countries? - Erich Gundlach; Ludger Wößmann (East Asian economic perspectives, 2004)
This paper examines determinants of educational performance in the high performing East Asian economies of Hong Kong, Japan, Singapore, South Korea, and Thailand by running within country regressions. The determinants considered include family background, school resources, and institutional characteristics of schools. Family background is found to be important, particularly in Korea. The class size appears to be positively associated with student performance, implying that putting in additional resources to reduce class size may not be an effective way to enhance the education sector?s productivity. al productivity. Such institutional characteristic of school as ?autonomy in teacher salary decision? is found strengthen student performance in Japan and Singapore. However, within country data provide limited variation in school institutional characteristics for the their effect to be precisely estimated. The results, despites their limitations, should be useful for future educational policy formulation not only in the East Asian countries examined but also in other developing countries.
Keywords: 330